2009
DOI: 10.1501/csaum_0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Küresel İklim Değişikliğinin Biyolojik Çeşitlilik ve Ekosistem Kaynakları Üzerine Etkisi: The effects of Global Climate Change on Biodiversity and Ecosystems Resources

Abstract: Özet: Fosil yakıt kullanımı, ormansızlaşma, tarımsal faaliyet vb. antropojenik etkinlikler, özellikle sanayi devrimiyle birlikte, metan, karbondioksit gibi doğal sera gazları emisyonlarında önemli ölçüde artışa neden olmuştur. Atmosferde sera gazları emisyonlarında meydana gelen bu artış doğal sera etkisinin bozulmasına ve atmosferin ısınmasına neden olmuş ve olmaya da devam etmektedir. Küresel ısınmanın potansiyel etkisi ise biyosferde küresel iklim değişikliğidir. Özellikle 1980'li yıllardan itibaren daha be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
(17 reference statements)
0
5
0
5
Order By: Relevance
“…e reaction of species to climate change, and consequently deteriorating climate parameters, such as precipitation and temperature at different levels, will lead to deterioration of the structure, productivity, and geographical disintegration of ecosystems (Aydın & Sarptaş, 2018;Öztürk, 2002). However, these conditions allow some plants to adapt; that is, some may succumb to competition or migrate due to climate change (Aydın & Sarptaş, 2018;Demir, 2009;Denhez, 2007;Erlat, 2014;Turkeş, 2016;Turkeş et al, 2000). erefore, analysis of the impacts of climate change on plants helps to develop strategic system models and tactical models for future action plans (Eppich et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e reaction of species to climate change, and consequently deteriorating climate parameters, such as precipitation and temperature at different levels, will lead to deterioration of the structure, productivity, and geographical disintegration of ecosystems (Aydın & Sarptaş, 2018;Öztürk, 2002). However, these conditions allow some plants to adapt; that is, some may succumb to competition or migrate due to climate change (Aydın & Sarptaş, 2018;Demir, 2009;Denhez, 2007;Erlat, 2014;Turkeş, 2016;Turkeş et al, 2000). erefore, analysis of the impacts of climate change on plants helps to develop strategic system models and tactical models for future action plans (Eppich et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study (Alp, 2006), snow melting is a determinant factor of primary flowering time of mountainous plants (Zafarian et al, 2019). Plants that blossom in winter and early spring and the ecological chain where they are located are negatively affected by a decrease in winter precipitation and an increase in winter temperature (Demir, 2009). akur and Chawla (2019) indicated that global warming severely affects species distributions and is believed to be a significant driver of species extinction due to species range shis (Braunisch et al, 2016;Franklin et al, 2016;Hof, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Aegean Geographical Journal https://dergipark.org.tr/tr/pub/ecd e-ISSN: 2636-8056 gazlarının emisyonlarındaki aşırı yükselme, yanlış arazi kullanımı, doğal çevrenin hızlı tahribatı ve ormansızlaşma iklim değişikliğine neden olan antropojenik kökenli faktörlerdir (Demir, 2009). Anlaşılacağı gibi "antropojenik" iklim değişikliğine yol açan insan kaynaklı değişkenleri tanımlamak için kullanılan bir terimdir.…”
Section: Ege Coğrafya Dergisiunclassified
“…(IPPC, 2007;Türkeş, 2008). After the industrial revolution, with the use of fossil fuels, a significant amount of greenhouse gases [carbon dioxide (CO2), methane (CH4), nitrogen oxide (N2O), ozone (O3) and fluorinated gases] began to accumulate in the atmosphere (Demir, 2009;Türkeş, 2012), and the increase in greenhouse gas accumulation has led to changes in the climate system. These changes were manifested most clearly by the increasing trend in air temperatures (Erlat & Ölgen, 2008).…”
Section: Introductionmentioning
confidence: 99%